Adjuvant transarterial chemoembolization to sorafenib in unresectable hepatocellular carcinoma: A meta‐analysis. Issue 2 (20th July 2020) - Chen, Anxin; Li, Shijie; Yao, Zhiyuan; Hu, Jiahao; Cao, Jiasheng; Topatana, Win; Juengpanich, Sarun; Yu, Hong; Shen, Jiliang; Chen, Mingyu
Abstract: Background and Aim: An increasing number of transarterial chemoembolization (TACE) plus sorafenib combination therapy has been applied for unresectable hepatocellular carcinoma (HCC). However, it remains controversial whether combination therapy is superior to sorafenib monotherapy. Therefore, we aimed to perform a meta‐analysis to evaluate the efficacy and safety of the combination therapy of TACE plus sorafenib for unresectable HCC. Methods: This meta‐analysis was based on the relative outcomes from a specific search of online databases between January 2008 and November 2019, and subgroup analyses were conducted to identify potential predictive factors. Results: A total of 3868 patients (TACE plus sorafenib vs sorafenib, 1181 vs 2687) were identified from nine studies, including one randomized controlled trial and eight retrospective cohort studies. The pooled results revealed that TACE plus sorafenib combination therapy significantly improves overall survival with the combined hazard ratio 0.74 (95% confidence interval [CI] = 0.66–0.84, P  < 0.001), time to progression (hazard ratio = 0.73, 95%CI = 0.65–0.82, P  < 0.001), and objective response rate (odds ratio = 2.19, 95% CI = 1.31–3.66, P  = 0.003). Subgroup analysis indicated that patients who developed macrovascular invasion achieve significantly great overall survival ( P for interaction = 0.001) with combination therapy, in contrast to nonmacrovascular invasion patients. In addition, no significant differences in adverse events were observed. Conclusion: This meta‐analysis demonstrated that TACE plus sorafenib combination therapy is superior to sorafenib monotherapy and should be recommended as an optimal treatment choice for unresectable HCC.